2020
DOI: 10.1038/s41598-020-58908-5
|View full text |Cite
|
Sign up to set email alerts
|

Locating induced earthquakes with a network of seismic stations in Oklahoma via a deep learning method

Abstract: The accurate and automated determination of earthquake locations is still a challenging endeavor. However, such information is critical for monitoring seismic activity and assessing potential hazards in real time. Recently, a convolutional neural network was applied to detect earthquakes from single-station waveforms and approximately map events across several large surface areas. In this study, we locate 194 earthquakes induced during oil and gas operations in Oklahoma, USA, within an error range of approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…Rather than other deep learning applications [7][8][9][10][11][12][13][14][15][16] where numerous earthquakes are tested, the current FMNet is only evaluated on four earthquakes with magnitudes larger than 5.4. This results from the limitation of historical moderate-to-large earthquakes that occurred in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than other deep learning applications [7][8][9][10][11][12][13][14][15][16] where numerous earthquakes are tested, the current FMNet is only evaluated on four earthquakes with magnitudes larger than 5.4. This results from the limitation of historical moderate-to-large earthquakes that occurred in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…When a destructive earthquake occurs, real-time reporting of the earthquake parameters is of crucial importance for immediate destruction assessment and emergency evacuations. Recent efforts have been re ned towards applying AI technologies to estimate the source parameters because of its full automation, high e ciency, and human-like capability [4][5][6] , which has been remarkably demonstrated in numerous seismic processing tasks such as earthquake detection 7,8 , seismic phase picking [9][10][11] , magnitude estimation 12 , and other tasks [13][14][15][16][17] . Besides reporting the three basic parameters of an earthquake (i.e., origin time, location, and magnitude), it is also exceedingly important to derive the source focal mechanism in time to better understand various aspects of the earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…The model is trained with events from a double-difference relocated catalog. Zhang et al [123] rely on a fully convolutional network to estimate a 3D image of the earthquake location, from data recorded at multiple stations. While location errors are small for earthquakes greater than magnitude 2, smaller events were reported to be more challenging to locate using this approach and associated with larger errors.…”
Section: Event Locationmentioning
confidence: 99%
“…A major effort in earthquake detection and location with ML algorithms has been focused on induced seismicity, either in geothermal fields [160], in mines [92], or in gas [103] and oil [91,100,101,113,123] extraction fields (in particular in Oklahoma). These studies aim at building automatic and more complete catalogs, and were described in Section 1.…”
Section: Induced Seismicitymentioning
confidence: 99%
“…For example, Moreb et al 19 used real-world data from a hospital in Palestine to apply a new framework that combined software engineering and machine learning for predicting health informatics. Another notable example is the assessment of seismic hazards, where the challenging problem of pinpointing small earthquakes (M L < 3.0) was addressed with a convolutional network that distinguished between certain events in a target zone 22 . Extensive experiments have further demonstrated that multimodal learning using visual images and remote sensing data can perform more accurate classification of large-scale bathymetric maps 23 .…”
mentioning
confidence: 99%